Incidence and Outcome of Hyponatremia in Children with Acute Bronchiolitis: A Prospective Observational Study. - Kumari, Neha; Raj, Richa; Singh, Om Prakash; Kumar, Mani Kant (Student’s Journal of Health Research Africa, 2026)
Background: Acute bronchiolitis is a leading cause of hospitalization in infants. Electrolyte disturbances, particularly hyponatremia, are increasingly recognized as markers of disease severity. Objectives: To determine the incidence of hyponatremia in children hospitalized with acute bronchiolitis and evaluate its association with disease severity and clinical outcomes. Methods: A hospital-based prospective observational cohort study was conducted in the Department of Pediatrics at Narayan Medical College and Hospital, Bihar, India, over one year. One hundred children aged 1 month to 2 years admitted with acute bronchiolitis were enrolled. Serum sodium was measured within 24 hours of admission. Hyponatremia was defined as serum sodium <135 mEq/L. Disease severity was assessed using the Bronchiolitis Clinical Score (BCS). Outcomes included duration of hospital stay, oxygen therapy, PICU admission, and mechanical ventilation. Results: Hyponatremia was observed in 32% of children. Most cases were mild (75%) and moderate (25%). Hyponatremia was significantly associated with higher BCS scores. Hyponatremic children had longer hospital stay (7.15 ± 1.4 vs. 4.92 ± 1.1 days; p<0.001), prolonged oxygen therapy (52.8 ± 12.4 vs. 34.6 ± 9.2 hours; p<0.05), higher PICU admission (15.6% vs. 4.4%; p=0.038), and increased mechanical ventilation (9.3% vs. 1.4%; p=0.045). Conclusion: Hyponatremia is common in hospitalized bronchiolitis and is associated with increased severity and adverse outcomes. Recommendation: Routine serum sodium monitoring, particularly in moderate to severe bronchiolitis, is recommended to aid early risk stratification and optimize fluid management.